The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.scitotenv.2012.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Role of iron species in the photo-transformation of phenol in artificial and natural seawater

Abstract: The role played by iron oxides (goethite and akaganeite) and iron(II)/(III) species as photosensitizers toward the transformation of organic matter was examined in saline water using phenol as a model molecule. The study was carried out in NaCl 0.7 M solution at pH 8, artificial (ASW) and natural (NSW) seawater, in a device simulating solar light spectrum and intensity. Under When NSW is spiked with phenol and iron oxides, Fe(II) or Fe(III), halophenols production is enhanced. A close analogy exists between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 45 publications
4
23
0
Order By: Relevance
“…In fact, the dissolved Fe(III) is often present as Fe(OH) 2þ in aqueous solutions, which can absorb solar irradiation (l > 290 nm) and yield $OH and Fe 2þ according to Eqs. (1) and (2) (Hammerschmidt and Fitzgerald, 2010;Calza et al, 2012). $OH could initiate the oxidative degradation of organic phosphorus to release phosphorus as reported (Shah et al, 2015;Fisher et al, 2006).…”
Section: Introductionmentioning
confidence: 74%
“…In fact, the dissolved Fe(III) is often present as Fe(OH) 2þ in aqueous solutions, which can absorb solar irradiation (l > 290 nm) and yield $OH and Fe 2þ according to Eqs. (1) and (2) (Hammerschmidt and Fitzgerald, 2010;Calza et al, 2012). $OH could initiate the oxidative degradation of organic phosphorus to release phosphorus as reported (Shah et al, 2015;Fisher et al, 2006).…”
Section: Introductionmentioning
confidence: 74%
“…A study performed on solutions spiked with Fe(II)/Fe(III) had shown that phenol disappearance rate was scarcely influenced by the presence/absence of precipitate iron (Calza et al, 2012). Similar considerations arose from the analysis of the data summarised in (Calza et al, 2012;Pelizzetti and Calza, 2002).…”
Section: Fe(ii)/fe(iii) and H 2 Omentioning
confidence: 77%
“…Similar considerations arose from the analysis of the data summarised in (Calza et al, 2012;Pelizzetti and Calza, 2002). Again, it implies that light absorption is needed to promote the phenol transformation.…”
Section: Fe(ii)/fe(iii) and H 2 Omentioning
confidence: 77%
See 2 more Smart Citations